2015
DOI: 10.1016/j.vaccine.2015.01.086
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced immune responses by skin vaccination with influenza subunit vaccine in young hosts

Abstract: Skin has gained substantial attention as a vaccine target organ due to its immunological properties, which include a high density of professional antigen presenting cells (APCs). Previous studies have demonstrated the effectiveness of this vaccination route not only in animal models but also in adults. Young children represent a population group that is at high risk from influenza infection. As a result, this group could benefit significantly from influenza vaccine delivery approaches through the skin and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…These data suggest that this enhanced response may be partly attributed to passively transferred maternal antibodies and partly to the developing immune system of the offspring. They also agree with a recent report from our group showing that young mice vaccinated with influenzacoated metal MNPs had improved IgG2a responses compared to IM vaccinated animals [57].…”
Section: Discussionsupporting
confidence: 93%
“…These data suggest that this enhanced response may be partly attributed to passively transferred maternal antibodies and partly to the developing immune system of the offspring. They also agree with a recent report from our group showing that young mice vaccinated with influenzacoated metal MNPs had improved IgG2a responses compared to IM vaccinated animals [57].…”
Section: Discussionsupporting
confidence: 93%
“…The HAI assay was performed as recommended by the World Health Organization (WHO) and the Center for Disease Control and Prevention (CDC) (44). In brief, sera and mucosal washes were treated with receptor destroying enzyme (RDE, Denka Seiken; Tokyo, Japan) overnight at 37 °C followed by RDE inactivation by incubating samples at 57 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…MNs were fabricated using biodegradable, polymer-encapsulated influenza vaccines and designed for penetration and dissolution into skin within several minutes (6). Many studies have demonstrated that delivery of influenza vaccines through skin by using various types of MNs generates enhanced immune responses and improves protective efficacy against viral infection when compared to conventional intramuscular injection (6, 7). In addition to enhanced immunogenicity, MN administration has been shown to be painless, skin lesion-free, and could be well accepted by healthcare providers and even handled by patients themselves (6, 8, 9).…”
Section: Introductionmentioning
confidence: 99%